Characterization of PVA-Enzyme Coated Indicator Electrodes GA coated again with PVC-KTpClPB-o-NPOE SEM-EDS, FTIR and XRD analysis - Abd Hakim S (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to characterize the tungsten-urea analyte indicator electrode. The method used is biosensor potentiometry with urease enzyme immobilization technique. This indicator electrode was coated with PVA-enzyme coated with glutaraldehyde (GA) 2.9% coated with PVC-KTpClPB- o-NPOE with o-NPOE variation of 61% and 66%. Characterization of coated indicator electrodes using SEM-EDS, FTIR and XRD analysis. A1-4 61% indicator electrode sample coated PVA-enzyme 1x coated with glutaraldehyde (GA) 2.9% 1x coated PVC-KTpClPB- o-NPOE 1x, with o-NPOE 61%. A3-4 61% indicator electrode sample coated PVA-enzyme 3x coated with glutaraldehyde (GA) 2.9% 1x coated PVC-KTpClPB- o-NPOE 1x, with o-NPOE 61%. Likewise, the reasoning of samples A1-4 66% and A3-4 66%. There are four indicator electrodes made with the notation A1-4 61%, A1-4 66%, A3-4 61% and A3-4 66%. The best results were obtained at the indicator electrode sample A1-4 61%, contributing to the urea sensor of the potentiometer cell